2021
DOI: 10.3906/sag-2102-202
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3: can it be a diagnostic tool for pneumonia in covid-19 patients?

Abstract: Background/aim: Biochemical markers are needed to show lung involvement in COVID-19 disease. Galectin-3 is known to play a key role in the inflammation and fibrosis process. We aimed to evaluate the predictive role of Galectin-3 levels for pneumonia in patients with COVID-19. Materials and methods:Total of 176 patients with COVID-19, confirmed with reverse transcriptase polymerase chain reaction, admitted to the Erzurum Regional Training and Research Hospital was analyzed. The study was designed as a cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Single-cell analysis found elevated levels of galectin-3 in monocytes, macrophages, and dendritic cells of patients with severe COVID-19 as compared to mild cases [81]. Serum galectin-3 concentrations were an independent predictor of severe outcome, which was defined as the need for invasive mechanical ventilation [82] and was also a predictor of severe pneumonia [78,84,86]. Furthermore, galectin-3 levels at admission were risk factors for the need of intensive care and advanced ventilatory support [87].…”
Section: Galectin-3mentioning
confidence: 99%
“…Single-cell analysis found elevated levels of galectin-3 in monocytes, macrophages, and dendritic cells of patients with severe COVID-19 as compared to mild cases [81]. Serum galectin-3 concentrations were an independent predictor of severe outcome, which was defined as the need for invasive mechanical ventilation [82] and was also a predictor of severe pneumonia [78,84,86]. Furthermore, galectin-3 levels at admission were risk factors for the need of intensive care and advanced ventilatory support [87].…”
Section: Galectin-3mentioning
confidence: 99%
“…In Baykan et al’s study, patients with a diagnosis of COVID-19 infection and typical and atypical pneumonia findings on thorax CT were evaluated and the usability of Galectin-3 level as a diagnostic tool in COVID-19 pneumonia was calculated. The results showed that Galectin-3 level was higher in patients with typical pneumonia findings on thorax CT [ 14 ]. In addition, the Galectin-3 level was found to be higher in the patient group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although a prospective study has been conducted to evaluate the role of Galectin-3 inhibitors in the treatment of COVID-19 previously, to the authors’ knowledge, there is no study examining the change of Galectin-3 protein level at the clinical level in COVID-19, and few studies have examined the usability of Galectin-3 level in the diagnosis of COVID-19 pneumonia [ 13 , 14 ]. This study aims to investigate the role of the Galectin-3 level in the diagnosis of COVID-19 pneumonia and the value of the Galectin-3 level in predicting the clinical course of the patient.…”
Section: Introductionmentioning
confidence: 99%
“… 71 In a study examining galectin-3 levels in COVID-19 patients, it was revealed that galectin-3 may be a diagnostic tool for typical pneumonia associated with COVID-19 and an indicator of the severity of pneumonia. 72 In a study investigating the effects of laboratory parameters on the prognosis of COVID-19, it was concluded that an increase in CRP, procalcitonin, erythrocyte sedimentation rate, ferritin, troponin, d -dimer, lactate dehydrogenase, and neutrophil count and a decrease in albumin, platelet, and lymphocyte count were associated with the severity of the disease. 73 In a similar study, prognostic laboratory parameters for COVID-19 were investigated in a group of geriatric patients with high mortality risk, and it was concluded that a high neutrophil/lymphocyte ratio was an independent risk factor for mortality.…”
mentioning
confidence: 99%